Application of whole exome sequencing in undiagnosed inherited polyneuropathies. Issue 11 (6th March 2014) - Klein, Christopher J; Middha, Sumit; Duan, Xiaohui; Wu, Yanhong; Litchy, William J; Gu, Weihong; Dyck, P James B; Gavrilova, Ralitza H; Smith, David I; Kocher, Jean-Pierre; Dyck, Peter J
Abstract : Background: Inherited polyneuropathies often go undiagnosed. We investigated whole exome sequencing (WES) in utility to identify the genetic causes of diverse forms of inherited polyneuropathies without genetic diagnosis. Methods: WES was applied to 24 cases from 15 kindreds. These kindreds had earlier unsuccessful candidate gene testing and five probands were initially thought to have acquired neuropathy. We assessed the efficacy of WES in screening 74 known neuropathy genes and 5195 reported pathogenic mutations for hereditary motor and sensory neuropathy, distal hereditary motor neuropathy, hereditary sensory and autonomic neuropathy, complicated hereditary spastic paraplegia, and select hereditary metabolic neuropathies. Results: Pathogenic mutations were identified in five kindreds: (1) ATL1-p.Val253Ile; (2) LITAF-p.Gly112Ser; (3) MFN2-p.Arg94Gln; (4) GARS-p.Ile334Phe; and (5) BSCL2-p.Ser 90Leu. Complexities in establishing inheritance, difficulties in selecting candidate genes and high cost of gene testing all hindered earlier gene discoveries. WES expanded the phenotypic spectrum of the identified known mutations. Possible causal mutations in known genes ( SPTLC1, DCTN1, REEP1 ) were identified in three kindreds. In the remaining seven kindreds, multiple rare or novel variants were identified in novel genes not previously linked with neuropathy. Our results demonstrate an average sequencing depth of 140×, >98% coverage and >10× sequencing depth for 93% (range 89%–96%) of the diverse neuropathy genes and their known mutations. Conclusions: Diverse inherited neuropathy patients without genetic discovery by candidate gene testing have a favourable probability of receiving a genetic diagnosis by WES. Frequently, atypical phenotypes account for earlier failed candidate approaches, and WES is demonstrated to expand the clinical spectrum of known pathogenic mutations.